SUBSTITUTION OF ALBITE BY SANIDINE: INFLUENCE OF THE DISTANCE BETWEEN MINERALS ON THE REACTION RATE - Alekseev V.A.; Medvedeva L.S. (My University, 2000)
Experiments in hermetic platinum capsules were carried out on the rate of the reaction (r) of sanidine for albite substitution (Ab → San) in 0.1 m KHCO3 solution (pH = 9) at 300°C and varying distance (L) between primary albite (Ab) grains and sanidine seeds (San). The value L was controlled by quartz (Qtz) grains, which played a role of an inert diluent of the reacting minerals. In all of the experiments, albite and sanidine grain sizes (0.05-0.1 mm), specific surfaces (0.11 m2/g), and weights of minerals (mg) per 1 ml of solution (Ab, 2.5; San, 10, and Qtz, 250) were maintained constant. At L> 10-3 m, the addition of sanidine seeds into the starting material did not affect the rate of the reaction Ab → San. At 25 μm < L < 1 mm, the value r (mol/kg s) changed as r =(1.4 ±0.3) × 10-10/L(0.42±0.02). This relationship can be explained in the context of one of two most popular hypotheses on the stage controlling reaction rate: diffusion of dissolved particles or kinetics of elementary surface reactions. However, the comparison of other characteristics of the reaction Ab → San with the criteria of distinction between the two hypotheses definitely supports the kinetic hypothesis. A drawback of the latter is the ignoring of surfacial forces, which play an important part at epitaxial growth. However, surface forces do not provide an adequate explanation of the derived dependency of r on L, because the distance of their action (10-6 m) is three orders of magnitude lower than the maximum distance at which this dependency was observed. A more plausible model is based on the hypothesis of microblock crystal growth. In this case, slow diffusion of colloid rather than dissolved particles in the solution could be the controlling factor of the rate of reaction Ab → San. These sanidine particles could form in the solution volume by homogeneous nucleation, diffuse then toward sanidine seeds, and attach to their surface in a regular orientation, realizing in such a way the mechanism of microblock growth.